GdFe-based nanostructured thin films with large perpendicular magnetic anisotropy for spintronic applications - Mohamed Salaheldeen; Valentina Zhukova; Mihail Ipatov; Arcady Zhukov (AIP Advances, 2024)
In this study, we investigated the impact of geometric factors on the magnetic anisotropy of Gd-Fe alloy thin films deposited on nanoporous alumina membranes. By synthesizing Gd-Fe alloy nanostructure thin films with different hole diameters (ranging from 45 to 90 nm) and keeping the layer thickness and lattice parameters fixed at 45 nm and 105 nm, respectively, we observed a significant perpendicular magnetic anisotropy (PMA) in samples with hole diameter above 65 nm. The transition from in-plane to out-of-plane magnetization in Gd-Fe alloy nanostructure thin films occurred at a critical antidot hole diameter of 75 nm. The observed variations in coercivity and remanence with the nanohole diameter are attributed to substantial changes in the magnetization mechanisms induced by the nanoholes. This novel induction of PMA in Gd-Fe alloy nanostructure thin films through the manipulation of geometric parameters in the antidot arrays opens new possibilities for tailoring the magnetic behavior of ferromagnetic metals with pronounced PMA.